Preventive self-care serious games for diabetes: a game design - Siti Normaziah, Ihsan; Tuty Asmawaty, Abdul Kadir; Benedict, R.; A. R., Abdullah (IOP Publishing, 2020)
Diabetes is a significant factor that contributes to obesity. In recent years, there has been an increasing number of patients, including adults and children diagnosis of diabetes. Extensive awareness has been carried out for educating people to prevent from diagnosed with diabetes such as sharing the information through electronic media, social media, forum by medical experts, and others. However, less implementation of awareness is given through entertainment computing, such as serious games to attract people to learn in a fun way. In order to overcome the problem, a serious game to prevent diabetes through awareness was developed, namely as Grab2BeHealthy to educate people in choosing healthy food. The primary purpose of this study is to design the game architecture for this serious game using SGDA framework. There are a few literature studies addressed on game design framework and the implementation of a serious game in the healthcare industry, especially for awareness and diseases prevention. The game design architecture was developed using game design framework as a guideline to meet the objective of prevention. The prototype development has been tested by 50 players to proof the game design architecture.